Fungsi Penyuluhan dalam Pembangunan Peternakan Sapi Potong Berkelanjutan - Priyono, Alex; Amam, Amam; Jadmiko, Mochammad Wildan; Harsita, Pradiptya Ayu (Universitas Galuh, 2025)
The extension system according to Law of the Republic of Indonesia Number 16 of 2006 is the entire series of developing abilities, knowledge, skills and attitudes of key actors and business actors through extension. The aim of the research is to examine the role of extension in the development of sustainable beef cattle farming. This research was carried out in Purnama Village, Tegalampel Sub-District, Bondowoso District, involving 122 micro-scale beef cattle farmers, who owned 1-5 beef cattle. The research location was determined deliberately with the consideration that Purnama Village is one of the villages assisted by the Universitas Jember for the development of smallholders beef cattle farming based on the Decree of the Chancellor of the Universitas Jember Number 4242/UN25/KL/2022. Research variables include the function of extension (X) and the five dimensions of sustainable livestock development, namely: ecological dimension (Y1), economical dimension (Y2), social and cultural dimension (Y3), institutional dimension (Y4), and technological dimension (Y5). Data collection was carried out using survey methods (interviews and filling out questionnaires), Focus Group Discussion (FGD), and observation. Research data was analyzed using simple linear regression using SPSS 26.0. The research results show that the role of extension has a significant effect on the ecological dimension by 17,20%, the economical dimension by 14.30%, and the social and cultural dimension by 14.40%, while the role of extension has no significant effect on the institutional and technological dimensions. The research conclusion shows that in general the role of extension has a positive influence on the five dimensions of sustainable livestock development.